Die gelehrte Korrespondenz der Brüder Pez, Text, Regesten, Kommentare, Band 2: 1716–1718, 2. Halbband - Wallnig, Thomas (2015)
This 1500-page volume contains the correspondence of the brothers Pez from 1716 lo 1718'. 557 letters , 256 of which have actually been preserved. These letters show the two historians, and monks of Melk abbey, successfully acquiring membership of the European Republic of Letters, but they also document first serious conficts within the monastery itself. The edition contains the entirety of the mostly Latin letter texts, extensive German summaries, commentaries and indices.